Reconstructing Late Cenozoic Stream Gradients from High-Level Chert Gravels in Central Eastern Kansas - Harbaugh, John W.; Merriam, Daniel F.; Howard, Hugh H. (Current Research in Earth Sciences, 2007)
Interpreting the evolution of Kansas’ landscape east of the Flint Hills provides major challenges. In the Neogene (late Tertiary) and perhaps part of the Pleistocene, streams transported a variety of sedimentary materials, including chert gravels derived from the Flint Hills. Gentle intermittent uplift stimulated the stream system to cut down, locally removing and reworking the gravels to create stream-terrace deposits that consist mostly of chert pebbles, which now lie well above the floodplains of modern streams. By correlating the elevations of these gravels, the gradients of the trunk streams that deposited them can be reconstructed. Interestingly, these ancient streams flowed southeast at a little more than a foot per mile (0.2 m/km), roughly the same as the gradient of the trunk streams in the region today. The evolving landscape in eastern Kansas also has been strongly influenced by an extensive network of fractures that is widespread in the midcontinent region and may be worldwide in extent. In northeastern Kansas, glaciation during the Pleistocene disrupted the southeasterly drainage and established the present location of the Kansas River. South of the Kansas River and its immediate tributaries, however, the general southeasterly drainage has been preserved. We have made use of the wealth of topographic-elevation data now available in digital form known as DEMs or digital elevation models. Coupled with GIS procedures, the DEMs helped link the mapped distribution of chert gravels with hypothetical fitted surfaces that represent ancient stream gradients. Furthermore, DEM data placed in shaded-relief map form emphasize the influence of fractures in evolution of the drainage system.